Nurses and Pharmaceutical Care: Interprofessional, Evidence-Based Working to Improve Patient Care and Outcomes - Dilles, Tinne; Heczkova, Jana; Tziaferi, Styliani; Helgesen, Ann Karin; Grøndahl, Vigdis Abrahamsen; Van Rompaey, Bart; Sino, Carolien G; Jordan, Sue (International journal of environmental research and public health, 2021)
Pharmaceutical care necessitates significant efforts from patients, informal caregivers, the interprofessional team of health care professionals and health care system administrators. Collaboration, mutual respect and agreement amongst all stakeholders regarding responsibilities throughout the complex process of pharmaceutical care is needed before patients can take full advantage of modern medicine. Based on the literature and policy documents, in this position paper, we reflect on opportunities for integrated evidence-based pharmaceutical care to improve care quality and patient outcomes from a nursing perspective. Despite the consensus that interprofessional collaboration is essential, in clinical practice, research, education and policy-making challenges are often not addressed interprofessionally. This paper concludes with specific advises to move towards the implementation of more interprofessional, evidence-based pharmaceutical care.
Keywords: Interprofessional Relations; interprofesionální vztahy; Cooperative Behavior; Humans; kooperační chování; Pharmaceutical Services; interprofessional collaboration; farmaceutické služby; Patient Care; péče o pacienta; zdravotní sestry; Patient Care Team; lidé; nursing; pharmaceutical care; Nurses; týmová péče o pacienty